CYSP: A new cylindrical directional neutron spectrometer. Conceptual design. (November 2015) - Gómez-Ros, J.M.; Bedogni, R.; Bortot, D.; Buonomo, B.; Esposito, A.; Gentile, A.; Lorenzoli, M.; Introini, M.V.; Mazitelli, G.; Moraleda, M.; Pola, A.; Sacco, D.
Abstract: This communication describes in detail the design of a new cylindrical neutron spectrometer (CYSP) embedding 7 active thermal neutron detectors in a moderating structure made of polyethylene, borated plastic and lead. The device provides a strong directional response within the energy interval from thermal to hundreds of MeV, being nearly insensitive to neutrons coming from directions other than the cylinder axis with energies up to about 10 MeV. Therefore it will be especially suitable for applications where the neutron spectrum as a function of the emission angle needs to be measured. The Monte Carlo transport code MCNPX has been used to reach the final configuration for the spectrometer in terms of size, collimator, and arrangement of borated plastic and lead layers, number and position of the detectors. Moreover, MCNPX has been also used to calculate the response matrix of the instrument. Highlights: Conceptual optimization design of a new cylindrical neutron spectrometer (CYSP). CYSP scattered neutron contribution is negligible at least below 10 MeV. CYSP response matrix has been calculated within an overall uncertainty of 3%.